Interest rate effects on output: evidence from a GDP forecasting model for South Africa - Aron, J; Muellbauer, J (University of Oxford, 2002)
Published in: Aron, J. and J. Muellbauer. 2002. "Interest rate effects on output: evidence from a GDP forecasting model for South Africa." IMF Staff papers 49 (November, IMF Annual Research Conference): 185-213.